Exploration of comprehensive two-dimensional liquid chromatography: Theoretical aspects and practical considerations - A tutorial - Katia Arena; Francesco Cacciola; Roberto Laganà Vinci; Paola Dugo; Luigi Mondello (Journal of Chromatography Open)
Comprehensive two-dimensional liquid chromatography (LC×LC) is a valuable tool for the analysis of very complex samples. LC×LC, which involves the coupling of two or more orthogonal separation systems, is a potential alternative to the conventional liquid-chromatography (1D-LC) approach. The profits of such a technique, compared to the 1D-LC approach, are the increased resolving power along with significant reduced ion enhancement or suppression phenomena in the MS source. This tutorial aims to provide detailed information on theoretical and practical aspects of the LC×LC approach with a particular focus on column combination, method optimization and separation performance. In addition, future perspectives and new trends are highlighted.